Invariance of a recovery capital scale across gender, ethnicity, and sexual orientation in a substance use disorder treatment program. (4th May 2019) - Hanauer, Matthew; Sielbeck-Mathes, Kathryn; Berny, Lauren
ABSTRACT: Background: Behavioral health care providers aim to see their clients achieve lifelong recovery from substance use disorders (SUDs). To do so, they must accurately assess incoming resources and barriers to recovery to identify areas of need for their clients. A recovery capital scale (RCS) is one way to identify these resources and barriers. However, there is limited evidence that RCSs are invariant across different demographics. Objectives: To evaluate whether a short 10-item RCS (SRCS-10) is invariant across gender (male versus female), ethnicity (white versus African American, Hispanic, and other racial identities) and sexual orientation (heterosexual versus non-heterosexual). Methods: The SRCS-10 is a shortened version of White's original unpublished 35-item RCS scale that was matched on items similar to the Brief Assessment of Recovery Capital (BARC-10). We used confirmatory factor analysis (CFA) to confirm unidimensionality and then conducted measurement invariance tests. Results: This study included 2751 females (67%) and 1341 males (33%) totaling 4092 clients from six large residential treatment centers. Using both exploratory factor analysis (EFA) and CFA the SRCS-10 has a large first to second eigenvalue ratio and had a CFI and TLI close to and above .9 with an SRMR of below .05 and an omega of .85. Additionally, we saw limited changes in key indicators such as the CFI and RMSEA across gender, race, and sexual orientation. Conclusions: These findings provide evidence that the SRCS-10 is a valid and reliable assessment across gender, race, and sexual orientation.